Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Is there an easier way to do a Taylor expansion of $e^{u^2+u}$ than do derivatives or substitute and then use Newton's binomial?

For example, expanding until the $4$th term:

$$e^{u^2+u}=1+u^2+u+ \frac{(u^2+u)^2}{2!} + \frac{(u^2+u)^3}{3!}+\frac{(u^2+u)^4}{4!}$$ $$e^{u^2+u}=1+u+\frac{3}{2}u^2+\frac{7}{6}u^3+\frac{25}{24}u^4+H.O.T.$$

I thought of using the $n$th derivative formula on $e^{u^2}\cdot e^u$ $$(f(x)\cdot g(x))^{(n)}=\sum_{n=0}^n{{n\choose k}f^{k}g^{n-k}}.$$

share|cite|improve this question

Perhaps an easier way is this:

Note first that $e^{u+u^2}=e^ue^{u^2}$. Now, we know power series for both of these functions: $$ e^u=\sum_{n=0}^{\infty}\frac{u^n}{n!},\qquad\text{and}\qquad e^{u^2}=\sum_{n=0}^{\infty}\frac{u^{2n}}{n!}. $$ From here, we use convolution: in the power series for $e^ue^{u^2}$, the coefficient by $u^k$ is precisely $$ \sum_{n=0}^{k}\left([u^n]e^{u^2}\right)\left([u^{k-n}]e^{u}\right), $$ where $[u^n]f(u)$ denotes the coefficient by $u^n$ in the power series expansion for $f$.

Now, $[u^n]e^{u^2}=0$ for all odd $n$; for even $n=2m$, the coefficient is $$ [u^n]e^{u^2}=[u^{2m}]e^{u^2}=\frac{1}{m!}. $$ On the other hand, the coefficient by $u^{k-2m}$ in $e^u$ is $$ [u^{k-2m}]e^u=\frac{1}{(k-2m)!}. $$ So, we have $$ [u^k]e^{u+u^2}=\sum_{n=0}^{k}\left([u^n]e^{u^2}\right)\left([u^{k-n}]e^u\right)=\sum_{m=0}^{\lfloor k/2\rfloor}\left([u^{2m}]e^{u^2}\right)\left([u^{k-2m}]e^u\right), $$ so that $$ [u^k]e^{u+u^2}=\sum_{m=0}^{\lfloor k/2\rfloor}\frac{1}{m!}\cdot\frac{1}{(k-2m)!}. $$ From here, you can of course try to do some simplification by breaking in to the cases where $k$ is even or odd, but I'll leave that to you.

share|cite|improve this answer

You could also multiply $$ e^u \cdot e^{u^2} = \sum_{n,k=0,1,\dots} \frac{u^{k} u^{2n}}{k! n!} = \sum_{n=0,2,\dots} u^n \sum_{k=0}^{n/2} \frac{1}{(2n-k)!k!} + \sum_{n=1,3,\dots} u^n \sum_{k=0}^{(n-1)/2} \frac{1}{(2n-k)!k!}.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.